Pengaruh Literasi Pajak dan Kesadaran Wajib Pajak terhadap Kepatuhan Bayar Pajak Orang Pribadi di Kelurahan Bukir Kota Pasuruan - M. Mascun Andianto; Sugeng Pradikto (Jurnal Manajemen Riset Inovasi, 2025)
The purpose of this study is to determine how individual taxpayer compliance in Bukir Village, Pasuruan City, is impacted by the degree of tax literacy and awareness. This study employs a quantitative methodology, causality design, and basic random sampling procedures with 22 participants. Questionnaires were used to gather data, and multiple linear regression was used for analysis. The study's findings suggest that taxpayer knowledge significantly influences tax compliance, while tax literacy has no discernible effect. According to this research, raising tax awareness rather than just tax literacy has a greater impact on promoting compliance. This study has significant ramifications for how the government can develop plans to increase tax compliance through initiatives for inclusiveness and tax knowledge.